2016
DOI: 10.1111/jssr.12244
|View full text |Cite
|
Sign up to set email alerts
|

Make Love and Lose Your Religion and Virtue: Recalling Sexual Experiences Undermines Spiritual Intentions and Moral Behavior

Abstract: In contrast with traditional considerations, sexuality is often perceived today as being rather compatible with religion/spirituality and morality. However, there may be some inherent opposition between (a) sexuality (thoughts, affects, and pleasure) and (b) religion/spirituality (attitudes, motives) and (interpersonal) morality (dispositions, behavior). The two imply, respectively, self-enhancement versus self-transcendence, disinhibition versus selfcontrol, and disgust indifference versus sensitivity. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Religion is considered as a primary way in which society regulates sexual behavior (Rigo, Uzarevic, & Saroglou, 2016). Because religious thought is heavily entwined with social and cultural norms (Davidson, Moore, & Ullstrup, 2004) it has been hypothesized that religion has an influence on whether university students chose to engage in hookups (Davidson et al, 2004).…”
Section: Collegiate Sexuality and Norms Of Casual Sexmentioning
confidence: 99%
“…Religion is considered as a primary way in which society regulates sexual behavior (Rigo, Uzarevic, & Saroglou, 2016). Because religious thought is heavily entwined with social and cultural norms (Davidson, Moore, & Ullstrup, 2004) it has been hypothesized that religion has an influence on whether university students chose to engage in hookups (Davidson et al, 2004).…”
Section: Collegiate Sexuality and Norms Of Casual Sexmentioning
confidence: 99%
“…Similarly, supraliminal religious priming invokes Belgian adults to more negatively evaluate erotic-simply sensual and semi-nude-pictures and dedicate less time to looking at them (Rigo & Saroglou, 2013). Inversely, immersion in a sexual mindset, through remembering one's personal sexual experiences, provokes Western Europeans to lower their spiritual interests and moral behavioral tendencies (Rigo, Uzarevic, & Saroglou, 2016).…”
Section: Religiosity and (Restricted) Sexualitymentioning
confidence: 99%
“…This disposition contrasts with what is at the heart of religiosity, i.e., a "moral muscle", self-control, and inhibitory resistance to temptations (Baumeister & Exline 1999;McCullough & Carter, 2013, for a review). In favor of the idea that religion and disinhibition are mutually exclusive, especially with regard to sexuality, evidence shows that disinhibition in puberty predicts religious doubt (Saroglou, 2012), and that a sexual experience decreases spiritual aspirations among those high in disinhibition (Rigo et al, 2016).…”
Section: Related Affects and Thoughtsmentioning
confidence: 99%
“…In addition to this, Durkheim asserts religion aids in the provision of meaning and purpose in the lives of individuals. Historically, religion has been a regulatory entity, used for social control measures against sexual behaviors and attitudes deemed to be a negative and untoward influence on society or the individual's being as a whole: physical, mental, and spiritual (Rigo, Saroglou, and Uzarevic (2016). And, while studies have supported religious influence on sexuality (Landor, Simons, Simons, Brody, and Gibbons 2011;Iveniuk, O'Muircheartaigh, and Cagney 2016), other studies have demonstrated a conflict between sexuality and religious values in which sexual desires have minimized the influence of religion on individuals (Rigo, Saraglou,and Uzarevic 2016;Legerski and Harker 2018).…”
Section: Religionmentioning
confidence: 99%